Transport property of multi-band topological material PtBi $$_2$$ 2 studied by maximum entropy mobility spectrum analysis (MEMSA) - Haijun Zhao (Nature Portfolio, 2021)
Abstract Electrical transport of both longitudinal and transverse directions carries rich information. Mobility spectrum analysis (MSA) is capable of extracting charge information from conductivity tensor, including charge types, concentration and mobilities. Using a numerical method based on maximum entropy principle, i.e., maximum entropy mobility spectrum analysis (MEMSA), mobility spectrum for $$β $$ β -type PtBi $$_2$$ 2 is studied. Three hole-pockets and two electron-pockets were found, including a small hole pocket with very high mobility, which is very likely corresponding to Dirac Fermions. Benefiting from our high resolution result, we studied temperature dependence of carrier properties and explained the sign change phenomenon of Hall conductivity. We further compared the results with band structure obtained by our first principle calculation. The present results prove MEMSA is a useful tool of extracting carries’ information in recently discovered Iron-based superconductors, and topological materials.